Infantile myofibromatosis in a 1-month-old male from Pakistan: A case report - Aiman Anjum; Malaika Jawaid Siddiqui; Nushrath Ali; Aisha Masoom; Arbaz Zaman; Eeshal Zulfiqar; Hussain Haider Shah (SAGE Open Medical Case Reports)
Infantile myofibromatosis is a well-recognized soft tissue tumor that is usually seen in infants and younger populations. These benign lesions mostly arise in the skin and soft tissues of the head and neck but may also involve visceral organs such as the lung, liver, and gastrointestinal tract. After a clinical diagnosis is made, a histological and immunological workup is performed to identify characteristic features like spindle-shaped cells and positive markers such as alpha-smooth muscle actin and vimentin. In most cases, since the mass is expected to spontaneously resolve, a wait-and-watch approach is adopted, especially in the pediatric age group. However, if the tumor advances to involve the organs, a complete surgical resection is carried out. In line with this, we present the case of a 1-month-old male who was diagnosed with infantile myofibromatosis after presenting with a congenital mass on the right thigh. He was born at 36 weeks of gestation to a healthy mother with an uneventful prenatal history. Imaging and histopathology confirmed the diagnosis, revealing a spindle cell neoplasm positive for alpha-smooth muscle actin and vimentin. Given the absence of visceral involvement, a conservative management approach was chosen, and the patient was scheduled for follow-up. However, the patient was lost to follow-up, which limited further assessment of disease progression. This case underscores the importance of early recognition and diagnosis of infantile myofibromatosis as a differential diagnosis for pediatric soft tissue masses. It also highlights the challenges posed by loss to follow-up in rare pediatric conditions.